PENGARUH BIAYA PROMOSI DAN BIAYA DISTRIBUSI TERHADAP HASIL PENJUALAN PRODUK BAWANG GORENG PADA UD BAWANG GORENG DI DESA PAGEDANGAN KECAMATAN ADIWERNA KABUPATEN TEGAL - Darnawi, Mrs.; Waskito, Jaka; Jalil, Mahben (PERMANA, 2018)
The purpose of this study is 1). To know the effect of promotion cost to the sale result, 2). To know the effect of distribution cost on sales result, 3). To know the effect of promotion cost and distribution cost together to the sales result. Data collection techniques used in this study is the method of documentation and interviews. While the data analysis method used is classical assumption test, simple linear regression analysis, test of simple linear regression coefficient, multiple linear regression analysis, test of multiple linear regression coefficient, coefficient of determination. Based on the results of simple linear regression analysis calculations obtained results for the promotion variable in obtaining a probability significance value of 0.000 is smaller than 0.05 means there is a significant effect of promotion on sales results concluded that the first hypothesis that reads